2020
DOI: 10.1098/rstb.2019.0547
|View full text |Cite
|
Sign up to set email alerts
|

Anthropogenic hybridization at sea: three evolutionary questions relevant to invasive species management

Abstract: Species introductions promote secondary contacts between taxa with long histories of allopatric divergence. Anthropogenic contact zones thus offer valuable contrasts to speciation studies in natural systems where past spatial isolations may have been brief or intermittent. Investigations of anthropogenic hybridization are rare for marine animals, which have high fecundity and high dispersal ability, characteristics that contrast to most terrestrial animals. Genomic studies indicate that gene flow can still occ… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 79 publications
0
39
0
Order By: Relevance
“…We observed stronger introgression asymmetries in contigs distinguishing Mediterranean and Atlantic M. galloprovincialis lineages compared to genome-wide trends in Batemans Bay, an observation consistent with M. edulis alleles influencing introgression barriers between introduced lineages (South Africa) and in secondary contact with native congeners (Batemans Bay). Genomic studies of marine invasive species and especially anthropogenic hybrid zones are still rare (Viard et al, 2016;Viard et al, 2020). The lack of strong reproductive isolation among M. galloprovincialis and M. planulatus provides a contrast to secondary contact in Ciona tunicates (Bouchemousse, Liautard-Haag, Bierne, & Viard, 2016;Viard et al, 2020) and oysters (Gagnaire et al, 2018) where reproductive isolation is strong.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We observed stronger introgression asymmetries in contigs distinguishing Mediterranean and Atlantic M. galloprovincialis lineages compared to genome-wide trends in Batemans Bay, an observation consistent with M. edulis alleles influencing introgression barriers between introduced lineages (South Africa) and in secondary contact with native congeners (Batemans Bay). Genomic studies of marine invasive species and especially anthropogenic hybrid zones are still rare (Viard et al, 2016;Viard et al, 2020). The lack of strong reproductive isolation among M. galloprovincialis and M. planulatus provides a contrast to secondary contact in Ciona tunicates (Bouchemousse, Liautard-Haag, Bierne, & Viard, 2016;Viard et al, 2020) and oysters (Gagnaire et al, 2018) where reproductive isolation is strong.…”
Section: Discussionmentioning
confidence: 99%
“…Genomic studies of marine invasive species and especially anthropogenic hybrid zones are still rare (Viard et al, 2016;Viard et al, 2020). The lack of strong reproductive isolation among M. galloprovincialis and M. planulatus provides a contrast to secondary contact in Ciona tunicates (Bouchemousse, Liautard-Haag, Bierne, & Viard, 2016;Viard et al, 2020) and oysters (Gagnaire et al, 2018) where reproductive isolation is strong. Thus, in introduced-native Mytilus hybrid zones there is the opportunity to observe the earliest stages of extensive admixture that may lead to consolidation into islands of divergence or to complete genomic swamping.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These inferences need to be carefully interpreted, as some studies have suggested that artificial transport blurs the DNA signatures that are used to study biological invasions (Rius et al, 2012;David, 2018). In addition, studies of genomics patterns of biological invasions increasingly report hybridization between previously isolated genotypes due to human activities (Chunco, 2014;Viard et al, 2020). Although the recent mixing of divergent genotypes may help non-indigenous species cope better with or adapt to novel conditions found in the introduced range (Bourne et al, 2018;Blakeslee et al, 2020), it considerably obscures the interpretation of phylogeographic results.…”
Section: Invasion Science and Phylogeographymentioning
confidence: 99%
“…While most studies of anthropogenic hybridization have focused on its consequences for native species (Allendorf et al, 2004; Beninde et al, 2018; McFarlane and Pemberton, 2019; Viard et al, 2020), an equally interesting situation arises when two introduced species find themselves in a novel geographic region. This scenario—rare now, but certainly becoming more common—provides an opportunity to study how isolating factors that are extrinsic (e.g.…”
Section: Introductionmentioning
confidence: 99%